Implementation of Tourism Place Branding Management in Indonesia through the 'Wonderful Indonesia' Campaign - Mutma, Fasya Syifa; Dyanasari, Reni (LSPR Institute of Communication & Business, 2025)
Tourism has become a significant sector in Indonesia's economy since 2019. Indonesia has a tourism brand managed by the Ministry of Tourism and Creative Economy (Kemenparekraf) called